2010
DOI: 10.1016/j.jacc.2009.08.057
|View full text |Cite
|
Sign up to set email alerts
|

Natural History and Expansive Clinical Profile of Stress (Tako-Tsubo) Cardiomyopathy

Abstract: In this large SC cohort, the clinical spectrum was heterogeneous with about one-third either male,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

34
700
18
47

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 801 publications
(799 citation statements)
references
References 27 publications
34
700
18
47
Order By: Relevance
“…Although initially regarded as a relatively rare disorder of little prognostic importance, TTC is emerging as a relatively common cause of cardiac disability in aging women 3,4 . In spite of occasional mortality, especially due to early development of cardiogenic shock, the majority of patients appear to be at little risk of cardiac events (other than recurrence of TTC) thereafter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although initially regarded as a relatively rare disorder of little prognostic importance, TTC is emerging as a relatively common cause of cardiac disability in aging women 3,4 . In spite of occasional mortality, especially due to early development of cardiogenic shock, the majority of patients appear to be at little risk of cardiac events (other than recurrence of TTC) thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…Takotsubo cardiomyopathy (TTC), also known as acute stress-induced cardiomyopathy, apical ballooning syndrome and "broken heart syndrome", is a form of regional left ventricular systolic dysfunction most commonly seen in aging women after physical or emotional stress [1][2][3][4] , which can be attributed to a dysfunctional myocardial reaction to high concentrations of catecholamines [5][6][7] . The classical course of TTC is "spontaneously reversible" left ventricular (LV) systolic dysfunction: initially hypokinetic/akinetic (usually apical) regions recover to apparently normal wall motion within days in most cases 8,9 .…”
mentioning
confidence: 99%
“…Standardized forms were used to collect patient data, including baseline characteristics, triggering factors (categorized as emotional or physical) (Fig. S2 in the Supplementary Appendix) 9 , cardiovascular risk factors, coexisting illnesses, results on electrocardiography and echocardiography, laboratory values, results on coronary angiography, use of medications, and use of critical care. Takotsubo cardiomyopathy was classified as apical, midventricular, basal, or focal (see the Methods section in the Supplementary Appendix).…”
Section: Study Populationmentioning
confidence: 99%
“…However, patients are at risk for recurrence even years after the first event, and data on in-hospital and longterm outcomes are limited. [7][8][9][10] The potential role of catecholamine excess in the pathogenesis of takotsubo cardiomyopathy has been long debated, 11 and as such beta-blockers have been proposed as a therapeutic strategy. 12 Nevertheless, to our knowledge, no prospective trials evaluating the therapeutic management have been reported to date.…”
mentioning
confidence: 99%
“…In the present patient, severe dyspnea may have induced takotsubo cardiomyopathy. Furthermore, β2 stimulants administered before and after admission may also have been an etiological factor (17). This is the first report of takotsubo cardiomyopathy in the patient with RPC.…”
Section: Discussionmentioning
confidence: 79%